Karakterisasi Ekstrak Herba Meniran (Phyllanthus niruri Linn) Dengan Analisa Fluoresensi - Harrizul Rivai; Refilia Septika; Agusri Boestari (STIFARM Padang, 2013)
Have done the manufacture and characterization of thick herba extracts meniran (Phyllanthus niruri Linn). Condensed extract is made using 96% ethanol solvent was concentreated by rotary evapolator. The observed character of the extract that is by fluorescence analysis. Fluorescence analysis performed on each fraction, methanol fraction, ethyl acetat fraction the fraction of water, kloroforom fraction, eter fraction in the test under UV 254 nm and 366 nm UV light whit the addition of reagents. The results obtained from the fraction of a significant color reaction is positive alkaloid characterized by a bright green color under UV light 254 nm, positive light yellow flavonoid under 366 nm UV lamp. In this study also tested the physic chemical.